Homochiral crystal generation via sequential dehydration and Viedma ripening. Issue 23 (24th March 2016) - Sivakumar, Reajean; Askari, Mohammad S.; Woo, Simon; Madwar, Carolin; Ottenwaelder, Xavier; Bohle, D. Scott; Cuccia, Louis A.
Abstract : Asymmetric amplification of conglomerate crystals formed via the dehydration of initially achiral crystals was achieved using Viedma ripening. Abstract : 1, 2-Bis( N -benzoyl- N -methylamino)benzene (2 ) forms centrosymmetric hydrate crystals (2· x H2 O) and non-centrosymmetric anhydrous crystals. Dehydration of this hydrate (30 min at 140 °C) resulted in the formation of chiral crystals ( i.e. a physical racemate of the conglomerate crystals) as verified using solid-state circular dichroism and powder X-ray diffraction. Subsequent attrition-enhanced deracemization, also known as Viedma ripening, was used to obtain homochiral crystals of2 within 5 h.